2011
DOI: 10.1016/j.neuroimage.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of M-channel subunits KCNQ2 and KCNQ3 in rat hippocampus

Abstract: Neuronal M-channels are low threshold, slowly activating and non-inactivating, voltage dependent K+ channels that play a crucial role in controlling neuronal excitability. The native M-channel is composed of heteromeric or homomeric assemblies of subunits belonging to the Kv7/KCNQ family, with KCNQ2/3 heteromers being the most abundant form. KCNQ2 and KCNQ3 subunits have been found to be expressed in various neurons in the central and peripheral nervous system of rodents and humans. Previous evidence shows pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 54 publications
0
48
0
Order By: Relevance
“…6a-c). As described previously 12,13,32 , we rather detected these channels at axon initial segments and nodes of Ranvier ( Supplementary Fig. 6d).…”
Section: Kcnq5 Expression In Pyramidal Cells and Interneuronsmentioning
confidence: 61%
See 1 more Smart Citation
“…6a-c). As described previously 12,13,32 , we rather detected these channels at axon initial segments and nodes of Ranvier ( Supplementary Fig. 6d).…”
Section: Kcnq5 Expression In Pyramidal Cells and Interneuronsmentioning
confidence: 61%
“…Importantly, our 'dominant-negative' strategy, in which all heteromeric channels containing one or more KCNQ5 subunit(s) are inactivated, avoided the possibility of the formation of more efficient KCNQ2/3 heteromers that may occur in Kcnq5 À / À mice. KCNQ2, -3 and -5 are broadly expressed in the brain and show robust expression in the hippocampus 13,19,32,33 . All three isoforms, as well as KCNQ2/3 and KCNQ3/5 heteromers, mediate K þ currents that slowly activate upon membrane depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Results from immunohistochemistry study have shown that KCNQ2/3 channels are localized to the axon initial segment (AIS) in hippocampus. 19) Electrophysiological recordings have demonstrated the functional involvement of KCNQ2/3 channels in hippocampal plasticity. Application or injection of KCNQ2/KCNQ3 channel blockers lowered the threshold for LTP induction 20,21) and reversed the cognitive impairment in animal models of cognitive disease.…”
Section: Discussionmentioning
confidence: 99%
“…M-channels are members of the Kv7 family of voltage-dependent K + channels and are expressed predominantly in neuronal cells, with the most abundant subunits being KCNQ2 (Q2) and KCNQ3 (Q3) (Brown and Adams, 1980;Wang et al, 1998;Jentsch, 2000;Robbins, 2001;Klinger et al, 2011). Although heteromeric Q2-Q3 channels are expressed in the cell bodies and dendrites of many hippocampal and cortical neurons (Marrion, 1997;Cooper and Jan, 2003) and also in the initial segment of several neurons (Devaux et al, 2004;Chung et al, 2006;Klinger et al, 2011), where they control neuronal excitability by limiting repetitive firing (Hille, 1992;Dolly and Parcej, 1996;Miller, 2000;Millar et al, 2007;Regev et al, 2009), exclusive expression of Q2 subunits can be found in nerve terminals, where homomeric Q2 channels might directly regulate neurotransmitter release (Cooper and Jan, 2003;Devaux et al, 2004;Martire et al, 2004;Peretz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although heteromeric Q2-Q3 channels are expressed in the cell bodies and dendrites of many hippocampal and cortical neurons (Marrion, 1997;Cooper and Jan, 2003) and also in the initial segment of several neurons (Devaux et al, 2004;Chung et al, 2006;Klinger et al, 2011), where they control neuronal excitability by limiting repetitive firing (Hille, 1992;Dolly and Parcej, 1996;Miller, 2000;Millar et al, 2007;Regev et al, 2009), exclusive expression of Q2 subunits can be found in nerve terminals, where homomeric Q2 channels might directly regulate neurotransmitter release (Cooper and Jan, 2003;Devaux et al, 2004;Martire et al, 2004;Peretz et al, 2007). In humans, mutations in KCNQ2 are associated with benign (BFNC; Biervert et al, 1998;Singh et al, 1998) and non-benign (encephalopathy; Weckhuysen et al, 2012) neonatal forms of epilepsy.…”
Section: Introductionmentioning
confidence: 99%